Optimization of Inulinase, Invertase and β-fructofuranosidase Production from Aspergillus niger TISTR 3570 by the Taguchi Method - Sirisansaneeyakul, Sarote; Songpim, Molnapat; Vaithanomsat, Pilanee (Agriculture and Natural Resources, 2012)
The medium conditions for inulinase, invertase and β-fructofuranosidase (bFFase) production from Aspergillus niger TISTR 3570 were optimized by the Taguchi method. Production of inulinase was most affected by inulin and the production of invertase and bFFase was most affected by pH. The maximum production of enzymes was achieved by employing a medium containing: inulin (50 g.L-1), yeast extract (12 g.L-1), MgSO4·7H2O (6 g.L-1) and an initial pH of 6. The inulinase was thermostable over a wide temperature range (25–80 ºC) and showed maximum activity at 70 ºC. In addition, activity was stable over the range pH 4–10 and the optimum for enzyme activity was pH 5. In contrast, invertase and bFFase were stable below 55 and 50 ºC, respectively, but showed highest activity at 65 and 60 ºC, respectively. Both enzymes were stable over the range pH 4–9 and had optimum activity at pH 4 for invertase and pH 5 for bFFase.